Influence of production system in local and conventional pig breeds on stress indicators at slaughter, muscle and meat traits and pork eating quality. (24th April 2015) - Lebret, B.; Ecolan, P.; Bonhomme, N.; Méteau, K.; Prunier, A.
<x content-type="archive" xml:space="preserve">Abstract</x> Sensory quality of pork is a complex phenotype determined by interactions between genetic and environmental factors. This study aimed at describing the respective influences of breed and production system on the development of pork quality. Plasma stress indicators and Longissimus muscle (LM) composition, physicochemical and sensory quality traits were determined in two contrasted breeds – the conventional Large White (LW, n=40) and the French local Basque (B, n=60). Pigs were reared in either a conventional (C; n=20 per breed), alternative (A; sawdust bedding and outdoor area, n=20 per breed) or extensive system (E; free-range, n=20 B). All the pigs from A and C systems were slaughtered at the same slaughterhouse, whereas B pigs from the E system were slaughtered at a local commercial abattoir. Major breed differences were found for almost all traits under study. LM from B pigs exhibited higher lipid, lower water and collagen concentrations, as well as lower collagen thermal solubility (P<0.001). Although plasma stress indicators at slaughter did not differ between breeds, except lower (P<0.05) lactate levels in B pigs, they exhibited higher LM pH1 and pHu values, and lower meat lightness, hue angle, water (drip, thawing and cooking) losses, glycolytic potential and shear force. Sensory analyses highlighted higher redness, marbling, tenderness, juiciness and flavour scores (P<0.01) of meat from B compared with LW pigs. Within both LW and B breeds, compared with C, the A system did not (P>0.05) influence plasma stress indicators, LM chemical composition and physicochemical or sensory traits of pork. In contrast, within the B pigs, the E system affected the meat quality more. Lower plasma cortisol levels (P<0.05), but higher plasma lactate, creatine kinase and lactate dehydrogenase activities, and more skin lesions (P<0.05), indicating higher muscular activity during pre-slaughter handling, were found in pigs produced in the E compared with the C system. E pigs exhibited higher meat pH1 and pHu values and shear force (P<0.01) and exhibited lower lightness, hue angle and drip and thawing losses (P<0.01) compared with the C pigs, whereas LM lipid, protein or collagen concentrations were not affected. Regarding sensory traits, the E system produced redder meat, but did not impact the eating quality of pork. Altogether, this study demonstrates that differences in meat quality between B and LW breeds can be modulated by extensive pig production system.